Social Media and Religious Moderation: Countering Radicalism Among University Students - Firdaus; Ibnu Imam Al Ayyubi; Nurhikmah; Rabiatul Nadawiyah (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
The rapid expansion of social media has transformed the way students access religious information and engage in public discourse, creating both opportunities and challenges in addressing digital radicalism. In this context, promoting religious moderation has become an important strategy for fostering tolerance and balanced perspectives among young people. However, empirical studies examining how social media influences students’ attitudes toward religious moderation remain limited. This study aims to analyze the role of social media in shaping and strengthening religious moderation among university students. Using a qualitative descriptive approach, the research involved university students who actively use social media platforms such as WhatsApp, Instagram, and TikTok. Data were collected through semi-structured online interviews and analyzed using thematic analysis. The findings reveal that social media plays a dual role: it facilitates exposure to diverse viewpoints that encourage openness, tolerance, and critical reflection, while simultaneously presenting challenges through the rapid circulation of provocative or extreme narratives. Students responded to these dynamics by developing digital literacy and critical filtering strategies to maintain balanced perspectives. This study contributes to the discourse on digital religion and education by highlighting how social media can function as a strategic platform for promoting religious moderation among university students in the digital era.